PENGARUH PENDIDIKAN KARAKTER DAN KESIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Lusiana Saparah; Dian Permana Putri; Rochanda Wiradinata (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2022)
Character education must be instilled in students in the learning process, especially in Economics subjects, so that it is hoped that students will be more ready to accept Economics subject matter and be able to understand the content of the material presented by the teacher, and be able to develop their knowledge more broadly. This study aims to determine whether there is an effect of character education and learning readiness on student learning outcomes in Economics subject at MA Basuraga Balerante Palimanan Cirebon. The method used in this research is descriptive research method with a quantitative approach. The results of the analysis in this study indicate that there is an influence between character education and learning readiness on student learning outcomes in the subject of Economics at MA Basuraga Balerante Palimanan Cirebon. From the results of the research that has been done, it can be concluded that the variable character education (X1) and learning readiness (X2) partially and simultaneously affect student learning outcomes (Y)